2020
DOI: 10.2147/dddt.s254948
|View full text |Cite
|
Sign up to set email alerts
|

<p>Effects of High-Dose Rosuvastatin on Ventricular Remodelling and Cardiac Function in ST-Segment Elevation Myocardial Infarction</p>

Abstract: To investigate the effects of high-dose rosuvastatin on ventricular remodelling and cardiac function in ST-segment elevation myocardial infarction (STEMI). Materials and Methods: From January 2017 to March 2019, the clinical data of 93 patients with STEMI were collected and analysed, with 46 cases in the conventional-dose group (rosuvastatin, 10 mg/d) and 47 cases in the high-dose group (rosuvastatin, 20 mg/d). Blood lipid (TC, TG, LDL-C and HDL-C), serum inflammatory markers (hs-CRP, IL-6, TNF-α and ICAM-1), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 44 publications
1
12
0
Order By: Relevance
“…This finding is consistent with Luo et al . (2020) [ 30 ]. High doses of rosuvastatin (20 mg/day; eight weeks) can significantly decrease serum levels of ICAM-1, IL-6 and TNFα in patients with ST-segment elevation myocardial infarction (STEMI).…”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent with Luo et al . (2020) [ 30 ]. High doses of rosuvastatin (20 mg/day; eight weeks) can significantly decrease serum levels of ICAM-1, IL-6 and TNFα in patients with ST-segment elevation myocardial infarction (STEMI).…”
Section: Discussionmentioning
confidence: 99%
“…While STEMI had a significantly increased number and mean proportion of ACS patients who had COVID-19 where it was 32 patients and the mean proportion was 76.2%, dyslipidemia had a significantly increased number and mean proportion of ACS patients who had not had COVID-19; 26 patients and a mean proportion of 54.2%. Unstable angina was observed only in the group of ACS patients who had not COVID-19 where their number was 17 and the mean proportion was 35.4% (see Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…A low value of HDL cholesterol is associated with left ventricle remodeling and diastolic dysfunction, especially in patients with hypertension, which is significant as the majority of the patients with OSA have it ( Horio et al, 2003 ). Regarding the potential benefits of lipid-lowering therapy, it is shown that high-dose statin therapy can improve blood lipid metabolism, reduce the inflammatory response, and prevent and treat ventricular remodeling and myocardial fibrosis ( Luo et al, 2020 ). These positive effects can significantly reduce cardiovascular risk and improve further prognosis.…”
Section: Discussionmentioning
confidence: 99%